(untitled) (Eurasian Medical Research Periodical, 2023)
On the basis of statistical diagnostic indicators, the spread of tuberculosis among the world’s population was studied. The data obtained will help improve the early diagnosis of patients with active tuberculosis and their provision of planned dental care